2011
DOI: 10.1016/j.bpj.2011.01.012
|View full text |Cite
|
Sign up to set email alerts
|

Lipid Lateral Organization on Giant Unilamellar Vesicles Containing Lipopolysaccharides

Abstract: We developed a new (to our knowledge) protocol to generate giant unilamellar vesicles (GUVs) composed of mixtures of single lipopolysaccharide (LPS) species and Escherichia coli polar lipid extracts. Four different LPSs that differed in the size of the polar headgroup (i.e., LPS smooth > LPS-Ra > LPS-Rc > LPS-Rd) were selected to generate GUVs composed of different LPS/E. coli polar lipid mixtures. Our procedure consists of two main steps: 1), generation and purification of oligolamellar liposomes containing L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
44
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(50 citation statements)
references
References 40 publications
6
44
0
Order By: Relevance
“…After sonication, LPS was double oxidized with galactose oxidase (57) followed by NaIO4 (58). The oxidized LPS was dialyzed using 2 kDa dialysis cassette against PBS (pH 7.4) buffer overnight with a minimum of 4 volume exchanges.…”
Section: Methodsmentioning
confidence: 99%
“…After sonication, LPS was double oxidized with galactose oxidase (57) followed by NaIO4 (58). The oxidized LPS was dialyzed using 2 kDa dialysis cassette against PBS (pH 7.4) buffer overnight with a minimum of 4 volume exchanges.…”
Section: Methodsmentioning
confidence: 99%
“…Multiple earlier studies have focused on the specific binding of LPS by ordered sphingomyelin/cholesterol-rich domains, so called rafts [11,12,30]. It was shown that in ternary systems which offer classical phospholipid bilayers next to rafts, LPS will partition with preference for the raft structures [11,12,30].…”
Section: Influence Of Lps On the Mechanical Performance Of Dmpc Membrmentioning
confidence: 99%
“…It was shown that in ternary systems which offer classical phospholipid bilayers next to rafts, LPS will partition with preference for the raft structures [11,12,30]. This selectivity may be induced by the highly saturated alkyl chains of the membrane-integrated part of the LPS leading to a preferred association with the more ordered rafts [11].…”
Section: Influence Of Lps On the Mechanical Performance Of Dmpc Membrmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have ranged from examining the formation, structure and physiochemical properties of LPS-containing vesicles in solution [8,9] and in dry and hydrated powders [10]. Neutron and X-ray diffraction studies have been used to examine suspensions and stacked bilayers of both smooth and rough LPS types [11,12].…”
Section: Introductionmentioning
confidence: 99%